2014
DOI: 10.1371/journal.pone.0112618
|View full text |Cite
|
Sign up to set email alerts
|

A Well-Circumscribed Border with Peripheral Doppler Signal in Sonographic Image Distinguishes Epithelioid Trophoblastic Tumor from Other Gestational Trophoblastic Neoplasms

Abstract: As epithelioid trophoblastic tumor (ETT) shares similar clinical features with other gestational trophoblastic neoplasms (GTNs), it is likely to be clinically misdiagnosed and subsequently treated in an improper way. This study aimed to identify the sonographic features of ETT that are distinct from other GTNs, including placental site trophoblastic tumor (PSTT) and invasive mole/choriocarcinoma (IM/CC). Here, we retrospectively analyzed ultrasound images of 12 patients with ETT in comparison with those of 21 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 18 publications
4
29
0
2
Order By: Relevance
“…10 Qin et al reported that Doppler ultrasound signals were observed only in the peripheral area of the tumor in 11 of 12 ETTs. 11 This ultrasound finding is consistent with the DCE-MR finding in our case. We attribute these findings to massive necrosis in the center of the tumor.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…10 Qin et al reported that Doppler ultrasound signals were observed only in the peripheral area of the tumor in 11 of 12 ETTs. 11 This ultrasound finding is consistent with the DCE-MR finding in our case. We attribute these findings to massive necrosis in the center of the tumor.…”
Section: Discussionsupporting
confidence: 92%
“…This correlation can serve as an important clue for the differentiation of ETT from other GTDs because most GTDs appear as hypervascular tumors on DCE‐MR images . Qin et al reported that Doppler ultrasound signals were observed only in the peripheral area of the tumor in 11 of 12 ETTs . This ultrasound finding is consistent with the DCE‐MR finding in our case.…”
Section: Discussionsupporting
confidence: 89%
“…Because of nonpenetrated by tumor cells, the intratumoral vessels of ETT are too small to be detected in Color Doppler image, or be just showed as low blood signals. [ 13 ] Same with Qin and colleagues’ finding, we identified a Doppler signal spotted around the tumor instead of within the tumor. This was distinct from IM and CC.…”
Section: Discussionsupporting
confidence: 76%
“…A specific US appearance that may aid in differentiating ETT from other types of GTN has been described as a well-circumscribed mass with sharp borders and a peripheral halo of low echogenicity at gray-scale US and peripheral increased vascularity at color Doppler US (41,42). However, this pattern is not characteristic of all cases of ETT, and lesions may demonstrate decreased vascularity (Fig 11) (42).…”
Section: Imaging Of Primary Tumormentioning
confidence: 99%